Importance of Faculty Involvement in Orientation - Michael J. Abel; Asheley Bice; Bradley E. Cox (Journal of College Orientation, Transition, and Retention, 2007)
Interaction with faculty is a critical element of the college student experience. Orientation is perhaps the first, and among the most valuable, opportunities for an institution to intentionally shape new student perceptions of the faculty. By carefully crafting faculty involvement in Orientation, an institution can present its faculty as active, engaged, and caring members of the campus community. This article discusses the literature and research surrounding faculty-student interaction, including the value of early interaction, the impediments to faculty involvement in Orientation, and the opportunities for faculty involvement in academic and social programs. The authors conclude that faculty participation in Orientation is beneficial, possible, and critical. Orientation professionals should seek out faculty to participate, as students will ultimately form opinions about the campus culture from their experiences at Orientation. Positive interactions between professors and students at Orientation can contribute to students’ ultimate success in college.